THE SIGNIFICANCE OF DIGITAL ANIMATION VIDEOS TO INSPIRE STUDENTS` COMMUNICATIVE COMPETENCE (TAMADDUN NURI JURNALI, 2025)
Communicative competence is the main purpose of achieving language proficiency. A number of methods and approaches have been suggested to implement in teaching methodology to develop communicative competence. Animated dubbing is one of the innovative pedagogical approaches, which can give opportunities for students to feel native speakers by substituting their voices. The study has suggested that animation can create a real language atmosphere for developing students` communicative competence.